Tips on when to request an imaging assessment (RMI, CT, or angiography) in a patient suffering from a headache - Aragão, Maria de Fátima Viana Vasco; Araújo, Luziany Carvalho; Valença, Marcelo Moraes (Headache Medicine, 2022)
This article is a mini-narrative review covering practical aspects of when to request an imaging evaluation of a headache patient. The vast majority of patients who seek help in a medical office receive as a diagnostic hypothesis one of the primary headaches, such as migraine, tension-type headache, or cluster headache. The vast majority of patients who arrive with a headache at the neurologist's office are migraineurs; individuals who suffer from tension-type headaches rarely seek the neurologist's help. In the emergency scenario, there is a more significant occurrence of secondary headaches when compared to patients treated in an outpatient clinic. In evaluating a patient with a headache, the physician should pay attention to red flags or signs that may indicate a secondary cause for the pain the patient reports. In primary headaches, with the exception of trigeminal-autonomic headaches, there is no need to investigate by imaging. In cluster headaches, in some cases, intracranial lesions may be found as the cause, mainly parasellar lesions such as cerebral aneurysms. Thus, image evaluation is indicated. Depending on the diagnostic suspicion in secondary headaches, different imaging examinations should be requested, the most frequent being MRI, CT, and angiography.Keywords: Headache, Magnetic Resonance Imaging, Tomography, X-Ray Computed, Migraine Disorders, Cluster Headache, Red flags